Burned Out Or Just Frustrated? Reasons Why Physical Education Teachers Leave Their Profession - Cieśliński Ryszard; Szum Ernest (Sciendo, 2014)
This work focuses on the reasons why physical education (PE) teachers leave their profession. The study included 80 individuals who decided to leave a teaching profession in 2013. A diagnostic poll method with the use of the QWL (Quality of Work Life) index was employed in the study. It was observed that there are usually a number of reasons why they give up their job, the most important being financial reasons. Their decision is influenced by the accumulation of professional and personal problems as well as their inability to solve them. The findings showed that teachers' departure from the profession is generally associated with the issue of burnout; however, financial reasons are most frequently ones that directly affect this decision.